Penguatan Peran Faith Based Organizations (FBO) dalam Pencegahan dan Penanggulangan HIV dan AIDS melalui Peran Aktif Young Relegiuos Leader di Tretes Prigen Pasuruan - Nyoko Adi Kusworo; Zainul Ahwan; Mukhid Mashuri; Mochamad Hasyim (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
Official data from the National AIDS Commission (KPA) showed that East Java ranks 2 (two) for most HIV. Whereas Pasuruan Regency was ranked as number 2 (two) the most cases of HIV and AIDS from all Regencies in East Java with 984 cases starting from 2000-2016. The majority of HIV cases were dominated by productive age (adolescents) between the ages of 20-29 years, the number of which reached around 300 people or around 32%. of the total HIV cases in Pasuruan Regency (KPA data of Pasuruan from 2000-2016). While in terms of data on HIV distribution by region, Prigen Subdistrict was ranked first with 82 cases. Responding to the issue, the role of the Faith Based Organization (FBO) was based on youth through the active role of Young Relegious Leader in Prigen Pasuruan was very encouraged to participate in HIV & AIDS prevention especially in adolescents. To support and strengthen the role of FBO in prevention of HIV and AIDS through efforts: to increase capacity building and knowledge of young religious leader on HIV and AIDS in medical and religion perspective, strengthening communication skills in social campaigns through the use of video blog media (VLOG), making HIV (AIDS) prevention materials (Modules) and building related partnership networks. The institutional strengthening of FBO was focused on Youth-Based FBO in Prigen Pasuruan which included Nahdlatul Ulama' (IPNU & IPPNU) Student Association, Muhammadiyah Youth Association (IPM) and representatives from Christian Youth in Prigen Pasuruan. Through strengthening this role, it was expected that the FBO would be able to prevent HIV/AIDS in members/congregations in their respective organizations in planned and independent manner. In addition, strengthening the role of FBO would also be a new movement of FBO in ​​Tretes Prigen area in taking responsibility for HIV and Narcotics issues in adolescents.